Guatemala : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1995)
This paper reviews economic developments in Guatemala during 1990-95. In 1993-94, output growth was led by a buoyant services sector while activities in the primary and secondary sectors slowed. Domestic demand grew strongly in 1991-92 owing to a substantial expansion in private investment and an increase in consumption. Growth of domestic demand slowed in 1993-94 because of sluggishness in private fixed capital formation. The rate of inflation fell from 60 percent in 1990 to 11 1\2 percent in 1993-94.